Deciding The Provisional Measures Regarding the Suspension of Criminal Procedure by International Centre for Settlement of Investment Disputes (ICSID) - Balcı, Murat; Aydın, Hüseyin; Çakır, Kerim (Anadolu Üniversitesi, 2024)
The Convention on the Settlement of Investment Disputes Between States and Nationals of Other States (hereafter referred to as the Convention), as well as the International Centre for Settlement of Investment Disputes (ICSID) was established within the framework of the Convention, aims to resolve disputes encountered in international investments in a prompt and facilitated manner under an independent credible judicial mechanism. ICSID tribunals can order provisional measures in a dispute presented before them to protect the parties’ mutual rights as mentioned in Article 47 of the Convention. The raison d’être for these measures is to ensure the integrity of the proceedings and exclusivity of the ICSID arbitration by preserving the status quo and preventing aggravation of the dispute. However, no explicit statement occurs in the Convention which sug-gests that the possibility of rendering a decision regarding provisional measures against a national criminal proceeding. Criminal proceedings are perhaps the most indisputable component of state sovereignty. Hence, the tribunals acknowledge a high threshold shall be required to justify an intervention in national criminal proceedings. Therefore, any intervention related to criminal proceedings that conflict with the sovereignty of a state authority should be evaluated case by case and kept at a minimum. In this context, the current paper will address the provisional measures that are orderable by IC-SID tribunals, the impact these measures have on pending criminal proceedings in domestic law. ICSID’s authority to impose sanctions on state parties if they do not comply with the measures in relation to the criminal proceedings. In addition, the article will evaluate requests for provisional measures to comprehend whether or not they intervene in the sovereign authority of a state party. We should also point out that, arbitration is a multidisciplinary subject, it has connections with International law, Constitution and other legal disciplines. However, the issue will only be han-dled within the scope of ICSID and criminal procedure.

Uluslararası uyuşmazlıklarda yaşanan artış geleneksel çözüm yollarına kıyasla uygulamada sağla-nan kolaylıklar sebebiyle yeni uyuşmazlık çözüm yollarının önemini artırmıştır. Türkiye’nin 1987’de imzaladığı “Devletler ve Diğer Devletlerin Uyrukları arasındaki Yatırım Anlaşmazlıkla-rının Çözümü için Sözleşme” (Convention on the Settlement of Investment Disputes Between States and Nationals of Other States) ve bu sözleşme esasları çerçevesinde kurulan Uluslararası Yatırım Anlaşmazlıkları Çözüm Merkezi (International Centre for Settlement of Investment Dis-putes-ICSID) uluslararası yatırımlarda karşılaşılan uyuşmazlıkların bağımsız ve güvenilir bir yargı alanında, kolay ve hızlı bir şekilde çözülmesini amaçlamaktadır. Sözleşmenin 47’nci mad-desinde belirtildiği üzere ICSID hakem heyeti tarafların karşılıklı haklarını korumak için uyuş-mazlıkla ilgili ihtiyati tedbirlere başvurabilir. Bu tedbirlerin özü, mevcut durumu muhafaza etmek ve uyuşmazlığın ağırlaştırılmasını engellemek suretiyle yargılamanın bütünlüğünü ve ICSID tahkiminin münhasırlığını korumaktır. Buna karşın cezai işlemlere ilişkin ihtiyati tedbir kararı verilebileceğiyle ilgili Sözleşmede net bir ifade bulunmamaktadır. Cezai işlemler, Devletin ege-menliğinin en tartışılmaz kısmını oluşturur. Hakem heyeti, cezai işlemlere müdahale için yüksek bir eşiğin gerektiğini kabul etmektedir. Bununla beraber, devletin egemenlik yetkisiyle çatışan, cezai işlemlere ilişkin bu tür müdahalelerin ayrıca değerlendirilmesi ve asgari düzeyde tutulması gerekir. Bu kapsamda çalışmada, ICSID tarafından alınabilecek ihtiyati tedbirler, bu tedbirlerin iç hukukta derdest olan ceza yargılamalarına etkisi ve cezai işlemlerle ilgili tedbir taleplerinin yerine getiril-memesi halinde ICSID’in taraf devletlere yaptırım uygulayıp uygula(ya)mayacağı izah edilecek-tir. Ayrıca ihtiyati tedbir taleplerinin taraf devletin egemenlik yetkisine müdahale niteliği taşıyıp taşımadığı değerlendirilecektir. Ayrıca belirtelim ki tahkim multidisipliner bir konu olduğu için çalışmanın Uluslararası hukuk, Anayasa ve diğer hukuk disiplinleri ile de irtibatı vardır. Ancak konu sadece ICSID ve ceza muhakemesi kapsamında ele alınacaktır.
Uluslararası Yatırım Anlaşmazlıkları Çözüm Merkezi’nin (ICSID) Ceza Muhakemesinin Durdurulmasıyla İlgili İhtiyati Tedbir Kararı Vermesi
Keywords: ICSID; Arbitration; Criminal Proceedings; Provisional Measures; Sovereignty; Tahkim; Cezai İşlem; İhtiyati Tedbir; Egemenlik